Does Adding Antibiotics to Cement Reduce the Need for Early Revision in Total Knee Arthroplasty? - Bohm, Eric (Springer US, 2013)
BACKGROUND: There is considerable debate about whether antibiotic-loaded bone cement should be used for fixation of TKAs. While antibiotics offer the theoretical benefit of lowering early revision due to infection, they may weaken the cement and thus increase the likelihood of aseptic loosening, perhaps resulting in a higher revision rate. QUESTIONS/PURPOSES: We (1) compared the frequency of early knee revision arthroplasty in patients treated with antibiotic-loaded or non-antibiotic-loaded cement for initial fixation, (2) determined effects of age, sex, comorbidities, and surgeons’ antibiotic-loaded cement usage patterns on revision rate, and (3) compared causes of revision (aseptic or septic) between groups. METHODS: Our study sample was taken from the Canadian Joint Replacement Registry and Canada’s Hospital Morbidity Database and included cemented TKAs performed between April 1, 2003, and March 31, 2008, including 20,016 TKAs inserted with non-antibiotic-loaded cement and 16,665 inserted with antibiotic-loaded cement. Chi-square test was used to compare the frequency of early revisions between groups. Cox regression modeling was used to determine whether revision rate would change by age, sex, comorbidities, or use of antibiotic-loaded cement. Similar Cox regression modeling was used to compare cause of revision between groups. RESULTS: Two-year revision rates were similar between the groups treated with non-antibiotic-loaded cement and antibiotic-loaded cement (1.40% versus 1.51%, p = 0.41). When controlling for age, sex, comorbidities, diabetes, and surgeons’ antibiotic-loaded cement usage patterns, the revision risk likewise was similar between groups. Revision rates for infection were similar between groups; however, there were more revisions for aseptic loosening in the group treated with non-antibiotic-loaded cement (p = 0.02). CONCLUSIONS: The use of antibiotic-loaded cement in TKAs performed for osteoarthritis has no clinically significant effect on reducing revision within 2 years in patients who received perioperative antibiotics. Longer followup and confirmation of these findings with other national registries are warranted. LEVEL OF EVIDENCE: Level III, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.